Proceedings of The6th International Conference on Mechatronics, Materials, Biotechnology and Environment (ICMMBE 2016) 2016
DOI: 10.2991/icmmbe-16.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stem cells in cancer therapy

Abstract: Abstract. Cancer stem cells (CSCs) have emerged as a population of cells that plays a vital role in recurrence of metastatic cancer, particularly resistant to chemotherapy and radiotherapy. In this article, we will discuss the correlation of CSCs with tumor immunology, microenvironment, long noncoding RNAs (lncRNAs) and tumor associated genes. These particular areas of discussion may help to identify novel strategies to target CSCs in future cancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A strong hypothesis that could explain the emergence of chemoresistant breast tumors is the maintenance of a minor quiescent population, namely, cancer stem cells (CSC). It has been demonstrated that TNBC patient tissues and cell lines present a higher abundance of CD44+/CD24-stem cells, as well as EMT-related gene signatures, than other subtypes, in line with the stemness phenotype (Park et al, 2010;Zhou et al, 2016;Shibue and Weinberg, 2017). Evidence of this phenomenon also comes from an increase in RNA transcripts, the expression of TGF-β1 and TGF-β type 1 receptors, and molecules associated with CSCs and EMT mechanisms in TNBC tumor biopsies after chemotherapy (Bhola et al, 2013).…”
Section: The Stemness Phenotypementioning
confidence: 99%
“…A strong hypothesis that could explain the emergence of chemoresistant breast tumors is the maintenance of a minor quiescent population, namely, cancer stem cells (CSC). It has been demonstrated that TNBC patient tissues and cell lines present a higher abundance of CD44+/CD24-stem cells, as well as EMT-related gene signatures, than other subtypes, in line with the stemness phenotype (Park et al, 2010;Zhou et al, 2016;Shibue and Weinberg, 2017). Evidence of this phenomenon also comes from an increase in RNA transcripts, the expression of TGF-β1 and TGF-β type 1 receptors, and molecules associated with CSCs and EMT mechanisms in TNBC tumor biopsies after chemotherapy (Bhola et al, 2013).…”
Section: The Stemness Phenotypementioning
confidence: 99%